2022
DOI: 10.1038/s41598-022-04868-x
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation and cell killing by milli- to nanosecond pulses and avoiding neuromuscular stimulation in cancer ablation

Abstract: Ablation therapies aim at eradication of tumors with minimal impact on surrounding healthy tissues. Conventional pulsed electric field (PEF) treatments cause pain and muscle contractions far beyond the ablation area. The ongoing quest is to identify PEF parameters efficient at ablation but not at stimulation. We measured electroporation and cell killing thresholds for 150 ns–1 ms PEF, uni- and bipolar, delivered in 10- to 300-pulse trains at up to 1 MHz rates. Monolayers of murine colon carcinoma cells exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 68 publications
3
47
0
Order By: Relevance
“…Nanosecond pulses and high-frequency biphasic pulses of a few microsecond duration (H-FIRE) 29 , 30 , 31 were suggested to limit neuromuscular stimulation and contractions. 15 , 16 Additionally, with nanosecond pulses, the possibility of thermal damage to the tissue is minimized 5 , 6 due to low energy being transferred to the treated area and electrochemical reactions are reduced. 8 ECT with nanosecond pulses has shown promising results 8 , 17 , 18 , 19 , but the underlying mechanisms of the observed decrease in cell survival and tumor regression remain to be explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosecond pulses and high-frequency biphasic pulses of a few microsecond duration (H-FIRE) 29 , 30 , 31 were suggested to limit neuromuscular stimulation and contractions. 15 , 16 Additionally, with nanosecond pulses, the possibility of thermal damage to the tissue is minimized 5 , 6 due to low energy being transferred to the treated area and electrochemical reactions are reduced. 8 ECT with nanosecond pulses has shown promising results 8 , 17 , 18 , 19 , but the underlying mechanisms of the observed decrease in cell survival and tumor regression remain to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, nanosecond pulses limit electrochemical reactions at the electrode-electrolyte interface 8 which may affect the treated medium or cells/tissues. [9][10][11] Although a much higher electric field strength is required to achieve a comparable biological effect, excitation thresholds appear to be higher than the electroporation thresholds with nanosecond pulses [12][13][14][15][16] , implying that shortening the pulse duration to nanosecond pulses could also reduce neuromuscular stimulation in electroporation-based applications.…”
Section: Introductionmentioning
confidence: 99%
“…An Anet A8 3D printer (Shenzhen Anet Technology Co) was modified to serve as an automated arm for accurate placement of a pair of stainless‐steel needle electrodes (0.61 mm diameter, 1.7 mm distance center to center), to facilitate the high‐throughput characterization of the PEF‐induced IRE areas in hESMC and hiPSC‐CM cultures (Casciola et al, 2020; Gudvangen et al, 2022). The heated stage of the 3D printer was used to maintain all wells of the 96‐well plate at 37 ± 1°C.…”
Section: Methodsmentioning
confidence: 99%
“…at different, likely lower, PEF exposures. Furthermore, PEF-induced electrical stimulation and reversible electroporation were also not considered, even though they can be achieved at lower EFTs than cell death (Gudvangen et al, 2022). Future studies are needed to detect PEF effects that were omitted in this tissue-specific focused report.…”
Section: Current Limitations and Future Impactsmentioning
confidence: 99%
“…With IRE, an antitumor effect can be achieved without use of any cytotoxic compound or anticancer drug. IRE alone causes dramatic changes in membrane and subsequently cellular homeostasis leading to cell death [ 1 , 3 , 13 ]. Many studies have demonstrated that IRE can be applied in vivo as nonthermal tissue ablation and tumor treatment [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%